Prevent Stunting with Information Communication and Education (KIE) Nutrition for Pregnant Women - Chairiyah, Royani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2024)
Efforts to prevent stunting in infants and toddlers can be carried out from the gestation period by increasing nutritional intake in pregnant women. Specific interventions aimed at children in the first 1,000 days of life (HPK) and contributing to a 30% reduction in stunting are Intake containing folic acid and iron is a very important combination of nutrients for pregnant women. The purpose of this community service activity is to increase the knowledge of pregnant women about Pregnant Women's Nutrition to prevent stunting in infants and toddlers with KIE (Communication, Information and Education. The method of community service implementation carried out in the form of balanced nutrition KIE for pregnant women at the Binawan University Laboratory on May 11, 2023. Data collection in the form of increasing the knowledge of pregnant women with questionnaires before and after KIE. The number of participants was 17 pregnant women. The results of the pretest service knowledge are 50% good, 20% moderate, 30% less. Posttest knowledge is good 70%, Fair 20%, Less than 10%. Conclusion There is an increase in pregnant women's knowledge about balanced nutrition so that stunting can be prevented. It is hoped that the Communication of Nutrition Information Education through the implementation of the Balanced Nutrition Guidelines can increase the nutritional knowledge of pregnant women, the intake of nutrients, especially Iron (Fe) and Vitamin C, and can reduce the risk of early stunting in toddlers.